The Creative Brain: Exploring the Connection Between Neuroscience and the Creative Process - Retno Ryani Kusumawati; Akhmad Baidun; Dery Kurniawan; Linus Kali Palindangan; Retika Najmamulat Asih (Journal of Social Research, 2026)
This research aims to explore and analyze the relationship between neuroscience and creative processes in order to gain a more comprehensive understanding of the neural mechanisms underlying human creativity. The method used was qualitative research with a descriptive approach through literature studies, with data collection techniques in the form of searching scientific literature from journal articles, academic books, and other credible sources, and analyzed using the stages of theme identification, data reduction, concept categorization, and inductive conclusion drawn. The results of the study show that creativity is a multidimensional neurocognitive process that involves dynamic interactions between various brain networks, especially the default mode network, executive control network, and salience network, which plays a role in the generation, evaluation, and implementation of ideas. In addition, creativity is also influenced by cognitive factors such as memory and thinking flexibility, as well as emotional and motivational factors such as mind wandering and flow conditions. These findings confirm that creativity is not singular or static, but rather the result of complex integrations between various neural systems and individual experiences. The implications of this research make an important contribution to the development of the theory of neuroscience of creativity and its application in the field of education and human resource development. Thus, this research strengthens the understanding that creativity can be studied scientifically and potentially developed through a neuroscience-based approach.